Integrative Yoga and Naturopathy Management of Lumbar Radiculopathy: case study - BELLAD, SHRISH PRABHAKAR; K, Archana; Shetty, Vanita (Indian Journal of Integrative Medicine, 2026)
Lumbar radiculopathy (sciatica) is a painful, debilitating condition characterized by excruciating pain, numbness, tingling, or burning sensations over the dermatomal course of the sciatic nerve distribution. It is usually caused by nerve root compression or irritation, disc herniation, vascular anomalies, or muscular or bony compression. We report the case of a 26-year-old male with the complaint of low back pain associated with pain radiating to the right leg. Based on clinical examination, it was diagnosed as lumbar radiculopathy. Yoga and Naturopathy interventions were given for 16 days in the outpatient ward. After the intervention, the pain gradually decreased. The Visual Analogue Scale (VAS) was reduced from 7 to 3. No adverse effects were observed during the treatment. Thus, this case showed that yoga and naturopathy have been shown to decrease the pain and frequency of symptoms of lumbar radiculopathy, recommending further future studies.